Pedagogic Competence of Physical Education Teachers in The Implementation of Revision Curriculum 2013 in Public Elementary Schools - Wijanarko, Agus; Mukarromah, Siti Baitul; Wahyu W, Imam Santosa Ciptaning (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The study aims to determine pedagogic competence teachers’ implementation of curriculum 2013 on learning Physical Education in Public Elementary School Kartasura district, Sukoharjo regency. The research method used in the study is a qualitative descriptive method. The data collection technique of this study uses observation, interview, and documentation techniques. The subjects of this study were Public Elementary Schools INTI in Kartasura district, Sukoharjo regency competence of Physical Education teachers in Curriculum 2013 was already very good at 87.5%. Pedagogical competencies of Physical Education’s teachers in the implementation of learning Curriculum 2013 were 82.5%; the category is very good. The pedagogic competence Physical Education’s teachers in learning evaluation Curriculum 2013 is categorized very well 80.5%, barriers faced by teachers in the implementation of Curriculum 2013 in learning Physical Education, namely the lack of teacher understanding of changes in the structure of Curriculum 2013, assessment systems, curriculum documents not available yet and the ability of Information and Communication Technology to Physical Education teachers. The conclusion of this study is the pedagogical competence of teachers in the implementation of the revised curriculum 2013 on the learning of Physical Education at Public Elementary School, Kartasura district, Sukoharjo regency, has been going well.